Effect Of Bypass Fat Supplementation on Growth, Onset of Puberty, Biochemical Metabolites and Reproductive Parameters in Jersey Crossbred Prepubertal Heifers - Debbarma, Kinkar (Indian Journal of Animal Nutrition, 2021)
Bypass fat can increase the energy density of ration without having any adverse effects on feed intake and digestion. The experiment was conducted to investigate the effects of supplementation of bypass fat on the onset of puberty in dairy heifers. The trial was conducted with 12 prepubertal divided into control (C) and Treatment (T) groups. The ration for the experimental animals in control group were not supplemented with bypass fat, whereas heifers in treatment group received bypass fat at 50g/day/h for a period of 150 days. Bypass fat supplementation significantly (P0.05) effect on the proportion of heifers attaining puberty (50.00 vs. 33.33%) as well as the age at onset of puberty (605.67Â±22.67 vs. 626.50Â±28.50 days). There was no significant (P>0.05) difference observed between the control and treatment groups in the mean size of dominant follicle, CL and ovary. The overall mean uterine horn diameter during the trial period was significantly (P0.05) in heifers during the study period. No significant (P>0.05) effect on plasma NEFA level was observed, however plasma glucose level was significantly (P